«Слово» митрополита Іларіона і Софія Київська – часовий і програмний взаємозв’язок - Нікітенко, Н. (Сiверянський літопис, 2025)
Метою статті є визначення дати виголошення «Слова про Закон і Благодать» першого мит- рополита-русина Іларіона та програмний перегук цього твору з архітектурою і стінописом Софії Київської. Методологічно робота здійснена на основі історико-літературознавчого, історіософ- ського та мистецтвознавчого підходів. Наукова новизна та висновки. «Слово» точно датується авторкою 1022 р. і містить численні смислові й програмні паралелі з архітектурою, мозаїками та фресками Софії (1011–1018). Обидві пам’ятки прославляють перемогу християнства у Русі та княже подружжя її хрестителів Володимира й Анну, які були ктиторами-засновниками Софії. У другій половині ХІІІ ст. Київський митрополит Кирило ІІ канонізував княжу пару християнізаторів Русі, замінивши в ній ім’я Анна на Ольгу як першу Київську княгиню-християнку. The purpose of the article is to determine the date of the pronunciation of the «Word on Law and Grace» by the first Rusyn Metropolitan Hilarion and the programmatic resonance of this work with the architecture and mural painting of St Sophia of Kyiv. Methodologically, the work was carried out on the basis of historical and literary studies, historiosophical and art historical approaches. Scientific novelty and conclusions. The «Word» is accurately dated by the author to 1022 and contains numerous semantic and programmatic parallels with the architecture, mosaics and frescoes of St Sophia (1011–1018). Both monuments glorify the victory of Christianity in Rus and the princely couple of its baptists, Volodymyr and Anna, who were the founding patrons of St Sophia. In the second half of the 13th c., Metropolitan Kyril II of Kyiv canonised the princely couple who Christianised Rus, replacing Annaʼs name with Olha as the first Christian princess of Kyiv.